Neuroendocrine Tumor Involving the Heart of a Dog - Oliveira, Acauã Belém Barreto Batista de; Aben-Athar, Carolina do Valle; Filho, Mário dos Santos; Bendas, Alexandre José Rodrigues; Suzano, Sara Maria de Carvalho; Balthazar, Daniel de Almeida; Carvalho, Vivian de Assunção Nogueira (Acta Scientiae Veterinariae, 2023)
Background: Neuroendocrine tumors are epithelial tumors with predominant neuroendocrine differentiation. Ectopic thyroid carcinoma develops in the ectopic thyroid parenchyma, in the anterior mediastinum, being an important differential diagnosis of paraganglioma, although occurring less frequently than the same. The cells invade the mediastinal fat reaching the adventitia of the aorta. There is a possibility of metastatic formations in the lung, kidneys, and pancreas. A supporting treatment was provided. The present study proposes the exposition and description of a case of neuroendocrine tumor in the heart, considering the rarity of the involvement of this tumor in the canine species. Case: A 9-year-old American Bulldog male canine was treated at home in the city of Rio de Janeiro. On clinical examination, dyspnea, edema of the hind limbs and an increase in abdominal volume were observed. With the suspicion of congestive heart failure, mainly on the right, cardiac exams were requested. Because it was an aggressive animal, sedation was performed with a combination of tiletamine and zolazepam. During cardiac auscultation, the presence of S4 was noticed, characterizing a gallop rhythm. No alterations were observed on the electrocardiographic examination. The echocardiogram showed a tumor mass in the atrium and dilation of the venous return vessels. The tumor enveloped 80% of the atrium of a 9-year-old male American Bulldog. The abdominocentesis procedure was performed to drain abdominal free fluid. Furosemide, enalapril and digoxin were prescribed as a treatment. Three months after the start of treatment, the animal presented intense dyspnea that culminated in the death of the patient, who later had the body sent for necropsy and subsequent tissue collection for histopathological analysis. Based on the immunohistochemical markers chromogranin and synaptophysin, the work here presented describes a case of a neuroendocrine tumor suggestive of paraganglioma involving a dog’s heart. Discussion: Brachycephalic dogs, such as Boxers, Bulldogs and Boston Terriers, are predisposed to the development of paragangliomas. The genetic predisposition is related to hyperplasia of the carotid bodies generated by chronic hypoxia, resulting from obstructive processes in the airways. As the reported dog is an American Bulldog, the possibility of the tumor in question was reinforced. Paragangliomas are more frequent in males from nine to thirteen years of age, commonly associated with other endocrine neoplasms. It is also an important marker present in paragangliomas. In contrast to the literature, the report points to a neuroendocrine tumor suggestive of paraganglioma, without eliminating the possibility of an ectopic thyroid tumor, because although TTF-1 appears in most thyroid tumors, not all of them are present, although it is very suggestive. Treatment in question, attributed to the control of right congestive heart failure, although with little effect, denotes that the obstructive process of the return pathway, even with the use of drugs that prevent congestion, did not delay the evolution of the disease. However, it is observed that the treatment resources for these tumors, whether by surgical or chemotherapy option, also have few answers. The lack of literature on ectopic thyroid tumors influences the diagnosis of paraganglioma. Thus, clinical and complementary findings, mainly along with immunohistochemistry, were essential in the diagnosis of neuroendocrine tumor. After 3 months of the start of the treatment, the animal died. Keywords: heart base tumor, Immunohistochemical diagnosis, heart, dog. Título: Tumor neuroendócrino em coração de cão Descritores: tumor neuroendócrino, diagnóstico Imuno-histoquímico, coração, cão.